Network Effects on Platform Markets. Revisiting the Theoretical Literature - Isabel Soares; Manuel Nieto-Mengotti (Scientific Annals of Economics and Business)
The characteristics of the bilateral network markets were already studied before 2003, but they focused on specific markets (credit cards or newspaper advertising) without relating implications with third parties. But since the emergence of new business models based on digital platform markets, especially since 2007 with the arrival of the smartphone, business scalability and network effects have skyrocketed. In this article, we carry out a review of the main contributions on network effects in the markets and their implications for the governance of platforms, which is of vital importance to understand the regulatory impacts when trying to limit the effects. negative effects of the market power. In the end, we found that in most studies, same-sided negative network effects are rarely considered, so despite multiple analyzes and empirical studies, there may still be some blind spots in the analysis of the network effects for the platform economies that can be transcendental for the understanding of all the market variables affected by the governance of platforms in monopolistic competition.